Про північно-східну границю Кросненської тектонічної зони в Українських Карпатах - Гнилко, О. (Геологія і геохімія горючих копалин, 2010)
Розглянуто структуру північно-східної частини Кросненського (Сілезького) покриву Українських Карпат. Відповідно до проведених автором геологічного картування та структурних досліджень північно-східна границя (фронт) Кросненського
покриву простягається від басейну р. Дністер (Розлуцька луска) до басейну р. Ріка
(Голятинська структура). Уздовж цієї границі виявлено меланж та олістострому.
Меланж представлений тектонітами пластичного та крихкого типів. Перший з них
розвивався в обводнених, а другий – у зневоднених літифікованих седиментах. До
фронту Кросненського покриву приурочена Голятинська структура, яка визначається як фрагмент Субсілезького покриву The results of investigating tectonic structure from the north-eastern margin of the
Krosno (Silesian) Nappe of the Ukrainian Carpathians are presented. The Krosno (Silesian)
tectonic unit occupies the central position of the Western Outer (Flysch) Carpathians nappe
pile and thrusted onto Skyba unit. In the western Polish sector of the Carpathians, the
Krosno Nappe is composed mainly of Upper Cretaceous turbidites (Istebna Formation).
Eastward the Ukrainian Carpathians this Nappe (namely Krosno too) is represented chiefly
by Oligocene-Miocene deposits (Krosno Formations). The strongly deformed SubSilesian Nappe, composed mainly of Upper Cretaceous–Eocene pelagic variegated marls, is
located along the northern and north-eastern margin of the Krosno Nappe.
According to the author’s geological mapping and structural research, the northeastern boundary of the Krosno (Silesian) Nappe of the Ukrainian Carpathians runs from
the basin of the Dniester river (Rozluch structural element) towards the Losyanec, Orava,
Plave, Ternavka, Volosyanka, Liskovets villages and farther southeast towards the basin of
Rika river (Holyatyn structural element). Holyatyn element is recognized as the fragment
of the Sub-Silesian Nappe. This boundary is the front of the Silesian Nappe. Along this
front the melange and olistostrome zones are discovered. Melange is represented both by
plastic and brittle types. The first of them was born in the watering sediment, the second
– was formed in the dewatered lithificated deposits. In the foreland of Krosno Nappe near
Rozluch and Yavora villages olistosthostrome crops out (basins of the Dniester river and
Stryi stream).
Thus, compresive tectonic events caused nappe thrust activity in the Carpathian Basin. Deformation zones propagated into watering sediments. As a result, sediments were
dewatered and strengthened, fault and shear-zones thickened. These proceses contributed
to the intensive formation of the melange in front of the thrust sheets (Krosno and other
nappes). Growing the Krosno Nappe, sliding and slumping the frontal part of this Nappe
into residual Skiba trough caused forming olisthostrome.